Search for doubly charged Higgs boson production in multi-lepton final states using 139 fb-1 of proton–proton collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (The European physical journal. C, Particles and fields, 2023)
A search for pair production of doubly charged Higgs bosons (H+-+-), each decaying into a pair of prompt, isolated, and highly energetic leptons with the same electric charge, is presented. The search uses a proton-proton collision data sample at a centre-of-mass energy of 13 TeV corresponding to an integrated luminosity of 139 fb-1 recorded by the ATLAS detector during Run 2 of the Large Hadron Collider (LHC). This analysis focuses on same-charge leptonic decays, H+-+- → l+- l'+- where l, l' = e, mu, tau in two-, three-, and four-lepton channels, but only considers final states which include electrons or muons. No evidence of a signal is observed. Corresponding upper limits on the production cross-section of a doubly charged Higgs boson are derived, as a function of its mass m(H+-+-) at 95% confidence level. Assuming that the branching ratios to each of the possible leptonic final states are equal, B(H+-+- → e+-e+-) = B(H+-+- → e+-mu+-) = B(H+-+- → mu+-mu+-) = B(H+-+- → e+-tau+-) = B(H+-+- → mu+-tau+-) = B(H+-+- → tau+-tau+-) = 1/6, the observed (expected) lower limit on the mass of a doubly charged Higgs boson is 1080 GeV (1065 GeV) within the left-right symmetric type-II seesaw model, which is the strongest limit to date produced by the ATLAS Collaboration. Additionally, this paper provides the first direct test of the Zee-Babu neutrino mass model at the LHC, yielding an observed (expected) lower limit of m(H+-+-) = 900 GeV (880 GeV).